Projectification within the Icelandic economy and the major industrial sectors - Margrét Eva Sigurðardóttir 1999- (2024)
Research on project management has noted an escalating trend of projectification, increasing across all sectors of the economy. The objective of this thesis is to review projectification within the Icelandic economy and provide a comprehensive understanding to which it is evident in various economic sectors. Furthermore, the thesis will explore industry specific differences and the monetary value of project work, as well as potential relationships between key financial aspects and the degree of projectification. The projectification within organisations was measured as the share of project work on total working hours. Understanding the share of project work and the economic value of projects is of great importance, as it enables organisations and economies to make informed decisions and adjust their strategic planning, resource allocation and organisational structure. It is also an important metric for understanding the societal impact of project management and can be beneficial for emphasising its significance. The results indicate that projectification within the Icelandic economy has been increasing over the years. This trend is expected to continue in the coming years, although to varying degrees between economic sectors, as some sectors have reached a level of saturation with their project work. There are evident differences in the level of projectification across economic sectors in Iceland as some sectors rely heavily on project-based work, while others have much lower levels of project involvement due to the nature of their operations. The results showed that the vast majority of projects are internal projects, rather than external projects. Only a few relationships were discovered between key financial aspects and projectification. Further examination and research are still needed for a more comprehensive understanding of these relationships. Rannsóknir á verkefnastjórnun hafa bent á vöxt í þróun verkefnavæðingar, sem hefur aukist þvert á alla geira hagkerfisins. Þessi ritgerð miðar að því að kanna ...